Faith as a Pillar: Parental Resilience and Spiritual Support in a Pediatric Cancer Shelter, Yogyakarta Indonesia - Muhammad Sulaiman; Waway Qodratulloh; Satria Kharimul Qolbi; Dony Darma Sagita; Toto Santi Aji; Yulius Tiranda; Rosih Aprilyani (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2026)
Childhood cancer places substantial psychological, emotional, and social burdens on parents as primary caregivers, especially when treatment requires prolonged accompaniment away from home. In this context, resilience becomes crucial, while spirituality may serve as an important source of meaning and strength. This study aimed to examine the level of parental resilience and to explore how spiritual experiences contributed to the formation and maintenance of resilience among families residing at the YKAKI pediatric cancer shelter in Yogyakarta, Indonesia. The study employed an explanatory sequential mixed-methods design. In the quantitative phase, data were collected from eight parents using the 25-item Connor-Davidson Resilience Scale (CD-RISC). Descriptive statistics were used to identify total and item-level resilience patterns. In the qualitative phase, semi-structured interviews were conducted with four purposively selected participants and analyzed thematically. The findings showed that parents demonstrated moderate to high resilience, with the strongest dimensions concentrated in belief in God, life purpose, and persistence, while adaptability and responses to uncertainty appeared less prominent. The qualitative findings revealed that spirituality functioned as a source of emotional steadiness, meaning-making, hope, and caregiving commitment, supported by communal interaction within the shelter. This study concludes that parental resilience in pediatric cancer caregiving is best understood as a spiritually mediated and socially supported process within a specific cultural setting.